Studi Komparasi Efektivitas Fatwa MUI Dan Qanun Aceh Terhadap Paylater Di Indonesia - Faruq, Saif Al; Ramadhan, Muhammad Hanif; Ar Romadhoni, Samil Basayev; Sasongko, Niwang Jati (Lisyabab : Jurnal Studi Islam dan Sosial, 2024)
This research argues that the paylater payment method in some e-commerce in Indonesia that contains usury is a violation in the perspective of Islamic shariah. However, we found differences and similarities between MUI Fatwa and Aceh Qanun in directing the Indonesian Islamic Community in general and the Aceh Province region in particular to direct the community in taking an attitude towards buying and selling transactions with the buy now pay later method or commonly called paylater.